The Effect Of Utilization Of Information Systems On Work Plans And Budgets On Employee Performance With Ease Of Use And Satisfaction Of Information System Users As Moderating Variables (Empiris Study at Universitas Sumatera Utara) - Wibowo, Hady; Sirojuzilam, Sirojuzilam; Puwoko, Agus (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this study is to analyze the effect of the ease of work plan and budget information systems on improving the quality of development human resources, the influence of satisfaction with the use of work plan information systems and budgets on improving the quality of development human resources, and the effect of application, ease and satisfaction of using work plan information systems and budget simultaneously to improve the quality of Human Resources Development. The research method used is quantitative method with data collection techniques by literature study, observation, and interviews and is supported by data collection tools, namely interview guidelines and questionnaires. The data analysis technique used multiple regression analysis. The results showed that the application of information systems has a positive and significant impact on the quality of human resources development at USU Medan; The ease of using the information system has a positive and significant impact on the quality of human resources development at USU Medan; Information system user satisfaction has a positive and significant impact on the quality of human resources development at USU Medan; and the application of information systems, ease of use of information systems and satisfaction of information system users together have a positive and significant impact on the development of the quality of human resources in the development of USU Medan.